PEMANFAATAN KOMBINASI FLY ASH BATUBARA, ALKILBENZENESULFONAT, DAN ZEOLIT PADAPENJERNIHAN MINYAK PELUMAS BEKAS DENGAN METODE PENJERAPAN - Risang Prasaji; Conny Dewita U; Herry Santosa (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
The using of mineral lubricating oils from petroleum fractionation happen in very fantastic number. Acording to data form central statistics agency republic of indonesia, the number of production of base oil for lubricant is 2.027.000 barrel in the year 2010. While the need of lubricating oil is 5.994.956 kl per year. On the one hand, increasingly depleted oil reserves so that the manufacture of lubricating oil (base oil) is also diminishing. Thus, research in order to reuse the used lubricating oil to be base oil is highly prospective.The research is intended to (a) determine the weight of fly ash as adsorbent that is relatively good, (b)determine the comparison volume of alkilbenzenesulfonat against weight of zeolit relatively good until obtained lubricating oil former which fullfill the criteria as base oilThe study is planned in two stages. First, the preparatory phase consisting of (a) the characterization of used lubricating oil viscosity based on the test and the% transmittance, (b) reduce and activate the natural zeolite. Second, adsorption and purification steps to remove contaminants in the form of a solid material, metal, and water.At this stage of adsorption experiments were performed by varying the weight of coal flyash each unit volume of used lubricating oil.At this stage ofpurification, experiments were performedby varyingthe weight ratioof zeoliteto thevolumeperunitvolumealkilbenzenesulfonateused lubricatingoil. At eachend of the experiment theresultswas tested againstthe absorbance ofthe lubricating oilviscosity.